Clinical and coprological assessment in symptomatic and asymptomatic subjects with infection with Blastocystis spp - Milagros del Valle Figueroa Lara; Daniela del Valle Cedeño García (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
To evaluate morphological, clinical and laboratory aspects in symptomatic and asymptomatic subjects with Blastocystis spp. 250 faecal samples were analyzed from individuals of the University Hospital "Antonio Patricio de Alcalá", Cumaná, Sucre state, with prior informed consent. Each fecal specimen was analyzed by direct examination, Ritchie and Kinyoun method; The quantification of the chromist was done in ten consecutive 40X fields, the morphometric analysis by fecal smears stained with Giemsa observed at 100X, measuring the structures by an ocular micrometer. Of the total of individuals evaluated 32.00% presented infection by the chromist, 31.25% with monoinfection with more than 5 parasites per field of 400X, of which 71.25% of them were symptomatic. The most identified morphotype was that of the central body, although in a single of liquid consistency, resistance morphotype was also identified, a finding that was not possible in the direct examination. Regarding the morphometric analysis, when evaluating the diameters of the morphotypes of the central body in patients with and without symptoms, by means of the non-parametric W Mann-Whitney test, the correspondence between them was evidenced (W= 5360,0; p<0,05). The morphological study, the quantification of the number of parasites per field and the use of complementary staining techniques, may contribute to optimize the laboratory diagnosis.